Generative ai tools in software teaching and learning: implications for business education - Jeyaraj, Anand; Sethi, Vikram (Journal of Management and Business Education, 2025)
The widespread introduction and availability of generative artificial intelligence (GenAI) tools have transformed how individuals use tools for their tasks. GenAI tools hide the complexities in tasks from individuals while allowing them to complete necessary tasks. Despite such advantages, it is unclear if they are desirable in learning environments since they disrupt the learning process as well as the outcomes. This paper shows how GenAI tools question the traditional teaching and learning process through the engagement, reinforcement, and assessment stages. Based on data preparation, data querying, and data processing activities taught in an undergraduate business course, this paper illustrates how GenAI tools impact learning by enabling students to skip problem-solving and critical thinking activities. While GenAI tools may yield productivity enhancements, they also further conditions in which individuals’ intellectual growth and lifelong learning capabilities may be compromised, thus weakening societies in the long run. The need to rethink traditional teaching and learning as blended methods to foster student learning is raised if GenAI tools are here to stay and expected to be used in educational settings.